2014
DOI: 10.1182/blood-2014-03-559591
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide inhibits the proliferation of CLL cells via a cereblon/p21WAF1/Cip1-dependent mechanism independent of functional p53

Abstract: Lenalidomide has demonstrated clinical activity in patients with chronic lymphocytic leukemia (CLL), even though it is not cytotoxic for primary CLL cells in vitro. We examined the direct effect of lenalidomide on CLL-cell proliferation induced by CD154-expressing accessory cells in media containing interleukin-4 and -10. Treatment with lenalidomide significantly inhibited CLL-cell proliferation, an effect that was associated with the p53-independent upregulation of the cyclin-dependent kinase inhibitor, p21 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 42 publications
2
62
0
1
Order By: Relevance
“…Equal amounts of total protein from each sample were fractionated by SDS-PAGE and blotted onto Cell proliferation assay. Primary CLL cell proliferation assay was performed as described (55). CLL cells were labeled by CFSE (Life Technologies) and plated at 1.5 × 10 6 /well/ml in a 24-well tray on a layer of irradiated HeLa CD154 cells (80 Gy) at a CLL/HeLa CD154 cell ratio of 15:1 in complete RPMI-1640 medium supplemented with 5 ng/ml of recombinant human IL-4 (R&D Systems) and 15 ng/ml of recombinant human IL-10 (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of total protein from each sample were fractionated by SDS-PAGE and blotted onto Cell proliferation assay. Primary CLL cell proliferation assay was performed as described (55). CLL cells were labeled by CFSE (Life Technologies) and plated at 1.5 × 10 6 /well/ml in a 24-well tray on a layer of irradiated HeLa CD154 cells (80 Gy) at a CLL/HeLa CD154 cell ratio of 15:1 in complete RPMI-1640 medium supplemented with 5 ng/ml of recombinant human IL-4 (R&D Systems) and 15 ng/ml of recombinant human IL-10 (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, cisplatin significantly reduced MDA-MB-231 cell viability at an IC 50 value of 7.8 µM. On the other hand, it is controversy and debatable whether lenalidomide can be used to control solid tumors (14,16), although lenalidomide significantly inhibited growth of the chronic lymphocytic leukemia cells (19). In the present study, we further confirmed that lenalidomide alone had only a minimal effect on MDA-MB-231 cell viability, even at a very high dose of 320 µM, far beyond the clinically achievable concentration in humans (20).…”
Section: Discussionmentioning
confidence: 88%
“…Subsequently, the use of lenalidomide in combination with dexamethasone was approved for MM patients who have received at least one previous treatment. Lenalidomide was also shown to inhibit chronic lymphocytic leukemia (CLL) cell proliferation via cereblon-p21-dependent manner [18]. More recently, pomalidomide, which has greater in vitro activity than thalidomide or lenalidomide [9], received approval for the treatment of relapsed and refractory MM.…”
Section: Crbn As a Binding Target Of Imidsmentioning
confidence: 99%